2019
DOI: 10.1097/anc.0000000000000558
|View full text |Cite
|
Sign up to set email alerts
|

Parent Engagement Correlates With Parent and Preterm Infant Oxytocin Release During Skin-to-Skin Contact

Abstract: Background: Preterm infants remain increasingly neurodevelopmentally disadvantaged. Parental touch, especially during skin-to-skin contact (SSC), has potential to reduce adverse consequences. Purpose: To examine relationships between parental engagement and salivary oxytocin and cortisol levels for parents participating in SSC intervention. Methods: A randomized crossover design study was conducted in a neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 25 publications
6
59
0
1
Order By: Relevance
“…In Hardin et al’s [ 43 ] study, for example, KC had moderate to significant effects on increasing oxytocin levels in mothers and infants at three months postpartum and decreasing cortisol reactivity in infants after acute stressor exposure. Identical results were obtained in the study of Cong et al [ 40 ] and Vitnner et al [ 57 ] for both maternal and paternal oxytocin levels. Indeed, Vitnner et al’s study showed how parents’ lower cortisol and higher oxytocin levels activated during SSC sessions were significantly related to pre-discharge parental involvement [ 57 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In Hardin et al’s [ 43 ] study, for example, KC had moderate to significant effects on increasing oxytocin levels in mothers and infants at three months postpartum and decreasing cortisol reactivity in infants after acute stressor exposure. Identical results were obtained in the study of Cong et al [ 40 ] and Vitnner et al [ 57 ] for both maternal and paternal oxytocin levels. Indeed, Vitnner et al’s study showed how parents’ lower cortisol and higher oxytocin levels activated during SSC sessions were significantly related to pre-discharge parental involvement [ 57 ].…”
Section: Discussionsupporting
confidence: 83%
“…Identical results were obtained in the study of Cong et al [ 40 ] and Vitnner et al [ 57 ] for both maternal and paternal oxytocin levels. Indeed, Vitnner et al’s study showed how parents’ lower cortisol and higher oxytocin levels activated during SSC sessions were significantly related to pre-discharge parental involvement [ 57 ]. Furthermore, rises in oxytocin levels and concurrent decreases in cortisol levels during SSC enable both infants and parents to develop a more synchronous relationship, improving bonding and attachment opportunities, especially in the challenging NICU environment [ 57 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Gentle stroking of rats increases Fos expression in the oxytocin-producing paraventricular nucleus of the hypothalamus (PVN), and increased plasma oxytocin levels are observed in rats following a wide variety of forms of peripheral sensory stimulation (Stock and Uvnäs-Moberg, 1988;Okabe et al, 2015). In humans, skin-to-skin contact (SSC) and KMC increase peripheral oxytocin levels in both parents and their infant (Vittner et al, 2019;Hardin et al, 2020). It is important to note that this effect is observed only when measured by enzyme immunoassay rather than radioimmunoassay, which may indicate a specific role for active fragments of oxytocin (Uvnäs Moberg et al, 2019); future studies should examine this discrepancy.…”
Section: Introductionmentioning
confidence: 99%